Endoscopic Assisted Septoplasty Versus Conventional Septoplasty;a Prospective Study - Hardy Sirwan Muhammed; Hiwa Asaad Abdulkareem (Advanced Medical Journal)
Background and objectives:Correction of deviated nasal septum underwent many modifications. Traditionally, it has been performed by using a headlight and nasal speculum and recently, endoscopic techniques have been used for septal surgery. As a consequence, the present study aimed to compare the efficacy of conventional and endoscopic septoplasty in treating septal deformity.